2014
DOI: 10.4102/sajems.v17i4.642
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between marketing intelligence and strategic marketing

Abstract: Despite the importance attached to MI and other marketing information functions, surprisingly few studies have explicitly examined the relationship between MI and strategic marketing decision-making. This article reports on a study conducted with the aim of determining the relationship between marketing intelligence (MI) and strategic marketing in South African organisations. A quantitative survey was conducted among 166 South African marketing decision-makers. The findings suggest a substantial gap between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…This result is corroborated with the findings of Venter and Rensburg (2014) which revealed that the availability of marketplace opportunity and intelligence (intelligence on customers, competitors and suppliers) has the greatest direct effect on perception of the overall quality of marketing intelligence and perhaps plays a mediating role, given its strong relationships with other categories of marketing intelligence.…”
Section: Discussion Of Findingssupporting
confidence: 81%
See 1 more Smart Citation
“…This result is corroborated with the findings of Venter and Rensburg (2014) which revealed that the availability of marketplace opportunity and intelligence (intelligence on customers, competitors and suppliers) has the greatest direct effect on perception of the overall quality of marketing intelligence and perhaps plays a mediating role, given its strong relationships with other categories of marketing intelligence.…”
Section: Discussion Of Findingssupporting
confidence: 81%
“…According to Venter and Rensburg (2014) in their study conducted to determine the relationship between marketing intelligence and strategic marketing in South African organizations. In the study, a quantitative survey was used among 166 South African marketing decision-makers.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Marketing intelligence classified into two categories frequently based on external data and internal data (Smith, 2011). Internal data marketing intelligence includes online transaction processing, clickstreams data and reports from internal sources, while external data includes primary sources, human intelligence, observation and secondary public domain sources (Venter & van Rensburg, 2014).…”
Section: Types Of Marketing Intelligencementioning
confidence: 99%
“…In the top of consumer centricity agenda, there are three important streams of research to be explored: the need of consumer driven orientation, co-creation of value and relational benefits (Spottle et al, 2016). In this context, relationship marketing arises as an organizational philosophy that enables firms to manage, develop and improve their interactions with consumers (Mishra & Mishra, 2009;Venter & van Rensburg, 2014) by transforming consumer information in decision-making processes, contributing to firms' positioning in the competitive scenario (Maçada, Brinkhues, & Freitas Junior, 2019).…”
Section: Introductionmentioning
confidence: 99%